Almeida Bible—Keeping a Heritage Alive: The Historical Path and Current Challenges of a Seventeenth-Century Translation - Cavaco, Timóteo (The Bible translator, 2023)
Until the seventeenth century, no Portuguese person or any other individual had either planned or accomplished a full translation of the Bible into Portuguese. As research has shown, there is a significant quantity of partial Bible texts in Portuguese during the late medieval period, but it was João Ferreira de Almeida (ca. 1628–1691) who undertook the “first common translation … of the Sacred Books.” Since the mid-eighteenth century, the “Almeida Bible” has been published in different versions, first in the Far East—Java and India—and, from the early nineteenth century, in Europe and America. This paper focuses on the historical context in which the Bible translation undertaken by João Ferreira de Almeida emerged and the main characteristics of the translation. It also provides a historical analysis of the revisions that the initial texts underwent in their different chronological and geographical environments, and ends with suggestions for a new revision of the European Portuguese version of the Almeida Bible.